Investigating factors influencing oil volatility: a GARCH-MIDAS model analysis - Le, Yiyi; Wen, Jing; Wu, Yuchen; Liu, Jia; Zhu, Yuchen (Frontiers in Energy Research, 2024)
This study explores the main factors influencing international oil price fluctuations, selecting five influential variables: the consumer price index (CPI), industrial production index (IPI), global rig count (ADU), economic policy uncertainty index (EPU), and geopolitical risk index (GRI) based on previous literature. Employing the GARCH-MIDAS model, this research analyzes comparative effects on WTI international oil prices. Our findings highlight the varying degrees of influence, with IPI showing a stronger impact and EPU indicating broader economic implications. The GRI index responds primarily to specific geopolitical events with delayed fluctuations. Our study's novelty lies in the empirical investigation using the GARCH-MIDAS model, offering valuable insights for policymakers to manage oil price volatility effectively, particularly by addressing economic policy uncertainty as a critical factor. We explored the main factors affecting the international oil price fluctuation through the previous literature, and selected 5 influencing factors for comparative analysis. They are the consumer price index, industrial production index, global rig count, economic policy uncertainty index and geopolitical risk index. Through empirical analysis, it is found that consumer price index and industrial production index have similar trends in terms of influence on WTI international oil, but in terms of influence intensity, industrial production index is higher. The economic policy uncertainty index has a more far-reaching impact, while the geopolitical risk index is based on specific geopolitical events. Its index fluctuation is later than that of WTI International oil, and its sensitivity is weak. The model loss function test with global drilling rig count as the low frequency variable has the lowest synthesis and the strongest sensitivity to WTI international oil price volatility.